2021
DOI: 10.3390/molecules26113476
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Antifungal Mechanisms of Thymol in the Human Fungal Pathogen, Cryptococcus neoformans

Abstract: Due to lifespan extension and changes in global climate, the increase in mycoses caused by primary and opportunistic fungal pathogens is now a global concern. Despite increasing attention, limited options are available for the treatment of systematic and invasive mycoses, owing to the evolutionary similarity between humans and fungi. Although plants produce a diversity of chemicals to protect themselves from pathogens, the molecular targets and modes of action of these plant-derived chemicals have not been wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…However, allyl structures and phenylpropanoids also constitute the phytochemical profile of some EOs [ 3 ]. EOs have been linked to antioxidant activity [ 4 ] as free radical scavengers and metal chelators [ 5 ], as well as to other biological activities such as anti-inflammatory, analgesic [ 6 ], sedative [ 7 ], antibacterial [ 8 ], antiviral [ 9 ], neuroprotective [ 10 ], and antifungal properties [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, allyl structures and phenylpropanoids also constitute the phytochemical profile of some EOs [ 3 ]. EOs have been linked to antioxidant activity [ 4 ] as free radical scavengers and metal chelators [ 5 ], as well as to other biological activities such as anti-inflammatory, analgesic [ 6 ], sedative [ 7 ], antibacterial [ 8 ], antiviral [ 9 ], neuroprotective [ 10 ], and antifungal properties [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thymol – HP-β-cyclodextrin microcapsules could control acid rot pathogen Geotrichum Citri-Aurantii in citrus fruits ( Serna-Escolano et al, 2020 ). The antifungal mechanism of thymol might be the inhibition of pathogen growth and spore germination, the direct effect on phospholipid and protein degradation ( Jung et al, 2021 ), and the inhibition of ergosterol biosynthesis to change the permeability of cell membrane and caused obvious damage to the cell wall and plasma membrane ( Galotto et al, 2016 ), cytoplasmic disintegration and organelle death ( Kowalczyk et al, 2020 ). In addition, some studies have shown that thymol can change cell membrane permeability and inhibit microbial growth by inducing membrane lipid peroxidation ( Nagoor Meeran et al, 2017 ), and it can also inhibit the growth of bocinia cinerea by destroying cell membrane morphology and causing electrolyte leakage ( Nazzaro et al, 2013 ; Folle et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…19 Terpenoid bekerja dengan cara memproduksi Reactive Oxygen Species (ROS) sehingga menimbulkan stress oksidatif dan menyebabkan sel jamur mati. 20 Fenol dapat menyebabkan terhentinya siklus sel pada jamur pada tahap replikasi sehingga mengganggu proses pembelahan sel dan menghambat pertumbuhan sel jamur. 18 Hasil penelitian Ningsih et al 15 yang menggunakan teknik difusi cakram mendapatkan bahwa ekstrak metanol daun mangga (Mangifera indica L.) memiliki kemampuan antijamur dengan konsentrasi 65 ppm dan 1000 ppm.…”
Section: Pendahuluanunclassified